EFFECT OF CROP ROTATION AND CHEMICAL SOIL TREATMENT ON BACTERIAL WILT OF POTATO - G. S. SHEKHAWAT, R. K. VERMA and (Indian Phytopathology, 2002)
Crop rotation and soil application of chemicals were tried for control of bacterial wilt of potato incited by Pseudomonas solanacearum. In a five-year crop rotation trial, potato wheat-lupin-maize-potato and potato-wheat potato-maize-potato rotations proved highly effective 'and reduced the disease incidence to 6.3 and 7.5 per cent, respectively in fifth year potato crop as compared to 80.1 per cent in the control. The tuber rot was also reduced to 9.5 and 12.9 per cent, respectively as compared to 62.2 per cent in check. Healthy produce increased by 194.1 and 150.4 per cent, respectively. Three years data revealed that preplant soil application of bleaching powder in furrows at 50 g/m2 controlled the disease by 68.4 per cent. Copper sulphate and bleaching powder applied at 15 g/m2 reduced wilt to half or less.